Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Trần Thế Kiệt

3/4-(3/5x+2)=(1/3-2/5x)+1/3

kaitovskudo
2 tháng 8 2016 lúc 13:11

=>\(-\frac{5}{4}-\frac{3}{5}x=\frac{2}{3}-\frac{2}{5}x\)

=>\(\frac{2}{5}x-\frac{3}{5}x=\frac{2}{3}+\frac{5}{4}\)

=>\(-\frac{1}{5}x=\frac{23}{12}\)

=>\(x=\frac{23}{12}:\frac{-1}{5}\)

=>\(x=\frac{-115}{12}\)


Các câu hỏi tương tự
Nguyễn Hà Linh
Xem chi tiết
ngo thu trang
Xem chi tiết
NiCo yAzAwA
Xem chi tiết
Tạ Thị Thùy Trang
Xem chi tiết
Anh Ngoc
Xem chi tiết
Trần Hoàng Nam
Xem chi tiết
Nguyenngocdiem
Xem chi tiết
Nguyenngocdiem
Xem chi tiết
Ngô Thần Uyển
Xem chi tiết